Aspects of the thermal ecology of the group-living lizard, Cordylus cataphractus : a spatial and temporal analysis - Truter, Johannes Christoff (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc (Botany and Zoology))--University of Stellenbosch, 2011.